Association of LOXL1 Gene Polymorphisms with Exfoliation Glaucoma Patients - Elham TAGHAVI; Ramin DANESHVAR; Zahra NOORMOHAMMADI; Seyed Mohammad-Hossein MODARRESI; Mohammad Reza SEDAGHAT (Tehran University of Medical Sciences, 2019)
Background: Pseudoexfoliation syndrome (XFS) is pathogenetically related to exfoliative glaucoma (XFG), which is the most common type of secondary glaucoma. We aimed to investigate the relationship between LOXL1 SNPs (rs1048661, rs3825942) and XFS and/or XFG in a cohort of Iranian subjects. Methods: This cross-sectional study investigated possible association between LOXL1 gene polymorphisms and exfoliative glaucoma in Northeastern part of Iran between May 2014 and May 2015. Sixty unrelated XFS/XFG patients, as well as 40 control subjects, were studied by direct sequencing. In fifteen senile cataract patients without glaucoma and fifteen patients with coexisting XFG and cataract, capsulorhexis specimen of the anterior lens capsule was used to evaluate LOXL1 gene transcripts by Real-Time PCR technique. We analyzed the results for allele frequencies and haplotype association and investigated the relative gene expression. Results: Significant associations between the rs382594 SNP and XFG and between rs1048661 SNP and XFG were observed (P<0.05 for both). The frequency of the G allele in the exonic SNP (rs1048661) appeared to be higher in XFS or XFG patients compared to control subjects (P= 0.0497). Moreover, in the rs3825942 SNP, the G allele was more frequent in XFS/XFG patients compared to control subjects (P=0.0016). The highest cumulative frequency was for the GG haplotype. GG haplotype was associated with increased risk of XFG compared to the rs1048661 G/T and rs3825942 G/A haplotypes. LOXL1 mRNA expression was not statistically significantly different between XFS/XFG and control subjects. Conclusion: We reported the LOXL1 gene polymorphism in an Iranian XFS/XFG cohort. Similar to many other ethnic groups and geographic regions, our results confirmed an association between LOXL1 gene variants and XFG in Iran.